2016
DOI: 10.1021/acs.analchem.5b04501
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Guidelines for Solid Phase Extraction of Suwannee River Dissolved Organic Matter

Abstract: This paper proposes improved guidelines for dissolved organic matter (DOM) isolation by solid phase extraction (SPE) with a styrene−divinylbenzene copolymer (PPL) sorbent, which has become an established method for the isolation of DOM from natural waters, because of its ease of application and appreciable carbon recovery. Suwannee River water was selected to systematically study the effects of critical SPE variables such as loading mass, concentration, flow rate, and up-scaling on the extraction selectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 45 publications
6
73
3
Order By: Relevance
“…The analytical window provided by the combination of PPL-SPE and FT-ICR-MS allowed us to examine a large, otherwise inaccessible portion of the DOM pool; in this study on average 67 ± 6% of the DOC was captured with our solid-phase extraction method. The PPL columns used here poorly recover very small and polar compounds (Raeke et al, 2016), but absorb a wide range of compounds of varying polarity and are thought to provide a major fraction of the natural DOM (Green et al, 2014;Li et al, 2016). The extraction efficiency did not significantly change along the salinity gradient of the estuary, indicating that our method captured a reproducible fraction of the estuarine DOM pool.…”
Section: Discussionmentioning
confidence: 90%
“…The analytical window provided by the combination of PPL-SPE and FT-ICR-MS allowed us to examine a large, otherwise inaccessible portion of the DOM pool; in this study on average 67 ± 6% of the DOC was captured with our solid-phase extraction method. The PPL columns used here poorly recover very small and polar compounds (Raeke et al, 2016), but absorb a wide range of compounds of varying polarity and are thought to provide a major fraction of the natural DOM (Green et al, 2014;Li et al, 2016). The extraction efficiency did not significantly change along the salinity gradient of the estuary, indicating that our method captured a reproducible fraction of the estuarine DOM pool.…”
Section: Discussionmentioning
confidence: 90%
“…6) identified using the SPE-SE method, among which 873 C c H h O o compounds were identified only in SPE-SE, exceeding the total number of C c H h O o compounds in SPE-1E by 49%. SRFA had fewer C c H h O o compounds identified than DOM extracted from Klasmann peat, especially in the regions of high H/C or high O/C, such as saturated aliphatic, carbohydrate and tannic-like compounds, likely due to the complicated extraction process of SRFA [21]. However, the characters of molecules in different eluted fractions were similar to those of DOM p (shown in Fig.…”
Section: Molecular Characterization Of C C H H O O Compounds In Dom Bmentioning
confidence: 92%
“…In particular, it can be seen from the enlarged region of m/z 575.04e575.10 ( Fig. 1D) that an excellent m/z separation of F 1 from F 3 , such as C 21 Table 1). Comparing the C c H h O o molecular formulas obtained, there were 1978 molecular formulas observed in both SPE-1E and SPE-SE, and 1213 molecular formulas observed only in SPE-SE.…”
Section: Molecular Characterization Of C C H H O O Compounds In Dom Bmentioning
confidence: 93%
See 1 more Smart Citation
“…Keil and Neibauer () found that hydrophile‐lipophile balance (HLB) sorbents obtain equal or better recoveries of free monomeric lignin phenols compared to C‐18 sorbents and liquid‐liquid extraction in various aquatic environments. Another common SPE cartridge, the styrene divinyl benzene polymer (PPL) cartridge, was found to more efficiently extract marine DOM than C‐18 cartridges (Dittmar et al ) and is widely used for ultrahigh‐resolution mass spectrometry (Kellerman et al ; Roth et al ; Lechtenfeld et al ; Li et al ; Raeke et al ).…”
mentioning
confidence: 99%